Requirements of juvenile Asian sea bass, Lates calcarifer Bloch, for lysine and arginine - Murillo, Deograce Pollan (College of Fisheries, University of the Philippines in the Visayas, 1995)
Two separate experiments were conducted to determine the dietary requirements of the juvenile Asian sea bass. Lates calcarifer Bloch, for the essential amino acids, lysine and arginine. Sea bass juveniles (initial average weight in lysine experiment, 13.1 g ; arginine experiment, 2.5 g) were given amino acid test diets that contained fish meal, zein, squid meal, and crystalline amino acids for 12 weeks. Each set of isonitrogenous and isocaloric test diets contained graded levels of lysine or arginine. Fish were fed twice a day at 0800 and 1600 h. In the lysine experiment, feeding rate was at 4 to 2.5% of fish body weight per day. In the arginine experiment, feeding rate was at 10% of body weight per day during the first four weeks and 4% thereafter. The fish were reared in 500-1 fiberglass tanks provided continuously with sea water (salinity, 30 ppt) at 4.1 1/min with a mean temperature of 28 C. At the end of each experiment, growth, survival, hepatosomatic index, and feed efficiency ratios were determined. Survival was high in fish given adequate lysine or arginine. Mean weight gains and survival rates were significantly different in fish fed varying levels of lysine or arginine, but no significant differences were found in the hepatosomatic index and feed efficiency ratio. The broken line analysis of the growth response showed that the dietary requirement of sea bass juveniles for lysine is 20.6 g/kg diet or 4.5% of the dietary protein. Arginine requirement is 18.2 g/kg diet or 3.8% of the dietary protein.